Distributed control and filtering for industrial systems - Mahmoud, Magdi S. (The Institution of Engineering and Technology, 2013)
Distributed control and filtering means the distribution of control and filtering capabilities throughout a system as opposed to central control in which control functions for a system are performed by a central computer (or by redundant, yet still centralized control computers). The rapid convergence of sensing, computing, and wireless communication technologies on cost effective, low power, miniature devices is enabling a host of new control applications. In recent years, we have witnessed wireless technologies replacing wired counterparts in all applications where it can be securely and reliably implemented. This book is about distributed control and filtering algorithms with particular emphasis on industrial applications.